Losy kobiet po Deklaracji Równości Płci. Przestrzenie i możliwości w cieniu ideologii Partii Węgierskiej - Takács, Izolda (Pedagogika Społeczna Nova, 2021)
The paper is part of a qualitative research project executed in 2017 and 2018, within the scope of which I have recorded semi-structured interviews with 11 female academics and 21 female doctors of science (DSc). I am attempting a comprehensive introduction of how historical changes in the second part of the 20th century affected the women’s and science policies, the educational and employment as well as family support system in Hungary, i.e. how the world presenting contradictory ideological and practical conditions due to the interrupted development of the middle class affected the structure of social roles. By quoting certain parts of the interviews, I intend to demonstrate the exact brand new and traditional issues female scientists have/could have faced during the era of state socialism.